Tending operation models for white poplar (Populus alba L.) stands growing under sandy soil conditions - Rédei, K.; Keserű, Zs.; Orlovic, S.; Galic, Z. (International Journal of Horticultural Science, 2016)
Integrated research aimed to intensify the practices of afforestation especially of white poplar and grey poplar woods. A new, simplified tending procedure has been developed to substitute earlier models considering the target diameter by right spacing as a tool to achieve adequat quality of logs. The practice-oriented model may help the qualitative improvement of white poplar growing technology in Hungary as well as in Serbia.